Records of Streblidae and Nycteribiidae (Diptera) on vespertilionid bats (Chiroptera : Vespertilionidae) from São Paulo State, Brazil - Graciolli, G.; Passos, F. C.; Pedro, Wagner André [UNESP]; Lim, B. K. (New York Entomological Soc Inc, 2002)
New records of five species of batflies (Diptera: Streblidae and Nycteribiidae) on vespertilionid bats are provided from S (a) over tildeo Paulo State, Brazil.